2020
DOI: 10.1002/admi.201901956
|View full text |Cite
|
Sign up to set email alerts
|

Material‐Dependent Antagonistic Effects between Soot and ZDDP

Abstract: While soot in engine oil is known to accelerate the wear of diesel and gasoline direct‐injection compression‐ignition engines, there is a lack of consensus on the wear mechanism though various hypotheses have been proposed in the literature. Particularly, some recently observed antagonistic effects between soot and a common lubricant antiwear additive, zinc dialkyldithiophosphate (ZDDP), while others did not. The discrepancy is, in part, explained by the strong alloy dependence of such antagonism discovered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…It should be noted that formation of soot particles is a complex process related to degradation of all components within the engine system. For instance, a recent study has suggested that carbonaceous nanoflakes can encapsulate the fragments of wear particles and inorganic products of mechanochemical reactions . Our current study sheds light on the chemistry occurring within these nanoscopic objects and provides precise information on (i) elemental distribution, (ii) nanoparticle morphology, and (iii) influence on applied operation processes.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…It should be noted that formation of soot particles is a complex process related to degradation of all components within the engine system. For instance, a recent study has suggested that carbonaceous nanoflakes can encapsulate the fragments of wear particles and inorganic products of mechanochemical reactions . Our current study sheds light on the chemistry occurring within these nanoscopic objects and provides precise information on (i) elemental distribution, (ii) nanoparticle morphology, and (iii) influence on applied operation processes.…”
Section: Resultsmentioning
confidence: 70%
“…For instance, a recent study has suggested that carbonaceous nanoflakes can encapsulate the fragments of wear particles and inorganic products of mechanochemical reactions. 47 Our current study sheds light on the chemistry occurring within these nanoscopic objects and provides precise information on (i) elemental distribution, (ii) nanoparticle morphology, and (iii) influence on applied operation processes. Given the generally accepted assumption that SNPs are potential toxic specimens, the abovementioned information is critical for toxicity assessment.…”
Section: ■ Experimental Sectionmentioning
confidence: 88%
“…The EF­(ZDDP+IL) tribofilm’s good resistance to contact fatigue micropitting may be attributed to two factors: (i) high content of phosphates and low content of sulfides and (ii) higher thickness (450 nm) to provide a better cushion upon contact. Phosphorus compounds are known to be wear-resistant whereas sulfur compounds could have a detrimental effect on the tribofilm. , The synergistic interaction between ZDDP and IL brings a higher concentration of triboactive elements to the solid–oil interface to form a thick zinc and phosphorus rich but sulfur-less tribofilm. Mechanical properties of the ZDDP, IL, and (ZDDP+IL) generated tribofilms were previously determined by nanoindentation .…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorus compounds are known to be wearresistant whereas sulfur compounds could have a detrimental effect on the tribofilm. 30,31 The synergistic interaction between ZDDP and IL brings a higher concentration of triboactive elements to the solid−oil interface to form a thick zinc and phosphorus rich but sulfur-less tribofilm. Mechanical properties of the ZDDP, IL, and (ZDDP+IL) generated tribofilms were previously determined by nanoindentation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%